Fuzzy based multi-criteria method for sustainable green chamber farming practices - SINGH, RAM KARAN; MALLICK, JAVED (The Indian Journal of Agricultural Sciences, 2019)
Ranking of vegetable cash crop is an important factor in the sustainable green chamber farming practices. In sustainable farming, a careful strategy based on the multi-criteria decision making is required. The present research stresses the cash crop ranking in the Saudi Arabia and takes into account wide standards linked with sustainable green chamber vegetable cash crop harvest. Considering the specialists' opinion and wide-ranging review of the literature, important criteria connected to sustainable green chamber agricultural practices apply for cash crops harvest. The twelve important criteria were chosen based on environmental conditions, social, economicand nutrient of soil for ranking the vegetable cash crops in the green chamber system modelled to attain the sustainability for the vegetable cash crop production. A mathematical model has been developed keeping in account the fuzzy-based multi-criteria method (FMCM). The model will also help the different stakeholder involved in the green chamber harvesting system and ministry of agriculture to develop the policies related to sustainable green harvesting practices and also improve the self-sufficiency of the farming sector subsequently improve the national gross domestic product.